Targeted blood brain barrier opening with focused ultrasound induces focal macrophage/microglial activation in experimental autoimmune encephalomyelitis - Schregel, Katharina; Baufeld, Caroline; Palotai, Miklos; Meroni, Roberta; Fiorina, Paolo; Wuerfel, Jens; Sinkus, Ralph; Zhang, Yong-Zhi; McDannold, Nathan; White, P. Jason; Guttmann, Charles R. G. (Frontiers in neuroscience, 2021)
Experimental autoimmune encephalomyelitis (EAE) is a model of multiple sclerosis (MS). EAE reflects important histopathological hallmarks, dissemination, and diversity of the disease, but has only moderate reproducibility of clinical and histopathological features. Focal lesions are less frequently observed in EAE than in MS, and can neither be constrained to specific locations nor timed to occur at a pre-specified moment. This renders difficult any experimental assessment of the pathogenesis of lesion evolution, including its inflammatory, degenerative (demyelination and axonal degeneration), and reparatory (remyelination, axonal sprouting, gliosis) component processes. We sought to develop a controlled model of inflammatory, focal brain lesions in EAE using focused ultrasound (FUS). We hypothesized that FUS induced focal blood brain barrier disruption (BBBD) will increase the likelihood of transmigration of effector cells and subsequent lesion occurrence at the sonicated location. Lesion development was monitored with conventional magnetic resonance imaging (MRI) as well as with magnetic resonance elastography (MRE) and further analyzed by histopathological means ...